2014
DOI: 10.1007/s10961-014-9332-4
|View full text |Cite
|
Sign up to set email alerts
|

Inter-temporal patterns of R&D collaboration and innovative performance

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 82 publications
(82 reference statements)
0
62
0
9
Order By: Relevance
“…Previous studies showed that firms involved in CWRO have higher innovation performance (Belderbos et al 2004(Belderbos et al , 2015Faems et al 2005;Nieto and Santamaria 2007). Specifically, Faems et al (2005) found that CWRO has a positive impact on new technology and product development, whereas collaboration with suppliers and customers is positively associated with improvements to current technology and products.…”
Section: Background and Hypotheses 21 Collaboration With Research Ormentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies showed that firms involved in CWRO have higher innovation performance (Belderbos et al 2004(Belderbos et al , 2015Faems et al 2005;Nieto and Santamaria 2007). Specifically, Faems et al (2005) found that CWRO has a positive impact on new technology and product development, whereas collaboration with suppliers and customers is positively associated with improvements to current technology and products.…”
Section: Background and Hypotheses 21 Collaboration With Research Ormentioning
confidence: 96%
“…Among various potential external collaborators, research organizations such as universities and research institutions are a key to gaining specialized scientific knowledge (Belderbos et al 2004(Belderbos et al , 2015Klevorick et al 1995). In addition, firms cooperating with research organizations can increase incoming spillovers 1 and minimize outgoing spillovers (De Bondt et al 1992;Röller et al 1997).…”
mentioning
confidence: 99%
“…Both product and process innovation are analysed by Fitjar and Rodríguez-Pose (2012), González-Pernía et al (2014), Nieto and Santamaria (2007) and Robin and Schubert (2013). R&D collaborations with universities or public research labs are most frequently investigated (Becker and Dietz, 2004;Belderbos et al, 2015;Broiwer andKleinknecht, 1996 González-Pernía et al, 2014), whereas citations are less frequently studied (Beise and Stahl, 1999;Jiang et al, 2010;Mansfield and Lee, 1996).…”
Section: The Determinants Of University-industry Collaboration and Unmentioning
confidence: 99%
“…The (Nieto and Santamaria, 2007;Belderbos et al, 2014). Moreover, exporting activities serve as a proxy for firms' foreign competitiveness (Herrera and Nieto, 2008).…”
Section: Model Specificationmentioning
confidence: 99%